Massive Subcutaneous Emphysema during Laparoscopic Cholecystectomy - Moosa, ASM; Islam, M Baharul; Akther, Shahina; Rahman, M Latifur; Ahmed, Nazim Uddin (TAJ: Journal of Teachers Association, 2009)
Laparoscopic surgical techniques are increasingly being applied to treat cholelithiasis and other indications of gallbladder diseases. These procedures however are not without potential morbidity. Herein we describe two patients treated with laparoscopic cholecystectomy; those cases were complicated with subcutaneous emphysema and hypercarbia per-operatively. After discontinuation of pneumoperitoneum, saturation of partial pressure of oxygen (SpO2) gradually increased with improvement of the neck subcutaneous emphysema, at the same time the lung ventilation also improved. Our findings show that we have to stop pneumoperitoneum or decrease partial pressure of end carbon dioxide level immediately, when we find a sudden increase of the peak airway pressure or decrease SpO2 with subcutaneous emphysema during laparoscopic cholecystectomy. doi: 10.3329/taj.v21i1.3225 TAJ 2008; 21(1): 77-79